2022
DOI: 10.1186/s12872-022-02878-1
|View full text |Cite
|
Sign up to set email alerts
|

A telemonitoring programme in patients with heart failure in France: a cost-utility analysis

Abstract: Background Certain telemedicine programmes for heart failure (HF) have been shown to reduce all-cause mortality and heart failure-related hospitalisations, but their cost-effectiveness remains controversial. The SCAD programme is a home-based interactive telemonitoring service for HF, which is one of the largest and longest-running telemonitoring programmes for HF in France. The objective of this cost-utility analysis was to evaluate the cost-effectiveness of the SCAD programme with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…After a full-text screening of the remaining 62 studies, we excluded 37 (60%; 21/37, 57% were classified as partial economic evaluations, such as cost analysis, containing only descriptions of costs; 10/37, 27% did not report outcomes specifically for HF; and 6/37, 16% were conference abstracts), resulting in 25 (40%) out of 62 studies for inclusion in the analysis. Two extra studies were identified from reference reviews; thus, 27 studies [ 31 - 57 ] were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After a full-text screening of the remaining 62 studies, we excluded 37 (60%; 21/37, 57% were classified as partial economic evaluations, such as cost analysis, containing only descriptions of costs; 10/37, 27% did not report outcomes specifically for HF; and 6/37, 16% were conference abstracts), resulting in 25 (40%) out of 62 studies for inclusion in the analysis. Two extra studies were identified from reference reviews; thus, 27 studies [ 31 - 57 ] were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the general characteristics of the included studies. Of the 27 studies, 13 (48%) were conducted using a decision analytical model [ 31 - 35 , 40 , 47 - 51 ], 13 (48%) used trial-based data [ 36 - 39 , 41 - 46 , 54 - 57 ], and 1 (4%) used a combination of both [ 41 ]. The majority of the studies (25/27, 93%) were from HICs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the cost-effective interventions could be unaffordable [46]. The cost-effective benefit may not be achieved if the implementation (internet infrastructure, servers, end-user devices and applications) is prohibitively expensive [47]- [49]. In addition, the few programs that start successfully may not always be sustainable in the long run, scalable, or transferable to other settings [50].…”
Section: Limitationsmentioning
confidence: 99%